Comparing phenotypic variation between inbred and outbred mice - Tuttle, Alexander H.; Philip, Vivek M.; Chesler, Elissa J.; Mogil, Jeffrey S. (Nature methods, 2018)
Inbred mice are preferred over outbred mice because it is assumed that they display less trait variability. We compared coefficients of variation and did not find evidence of greater trait stability in inbred mice. We conclude that contrary to conventional wisdom, outbred mice might be better subjects for most biomedical research.